HUBUNGAN ANTARA KONSUMSI MINUMAN BERKAFEIN DENGAN POLA TIDUR PADA MAHASISWA TEKNIK - Selly Oktaria (JURNAL KESMAS DAN GIZI (JKG), 2019)
Caffeine in low doses is able to provide positive and negative effects on a person's body. The main pharmacological effects of caffeine is adenosine receptor antagonist that may affect the functioning of the central nervous system and can interfere with sleep quality and will affect sleep patterns, sleep should be important to maintain physical health, mental and emotional. This study aims to determine the relationship between the consumption of caffeine on sleep patterns. This research use analytical method with cross sectional approach. The population are all students of Faculty of Civil Engineering ITM of 2014. With total sampling technique, amounting to 142 students. Methods of data collection using primary data and interviews. This study showed that 34 students who did not consume caffeine, there were 12 (35,3%) students had bad sleep pattern, while 22 (64,7%) students had good sleep pattern. Based on the results of chi-square test, it is concluded that there is a significant relationship between caffeine consumption to sleep patterns.